PERBANDINGAN CIRI ANATOMI KAYU DAN KULIT 3 JENIS PULAI (Alstonia sp.) - Andianto (BRIN Publishing, 2011)
Pulai (Alstonia sp.) belonging to the family Apocynaceae, produces latex which is frequently used as a traditional medicine. Various literatures on medicinal tree species frequently mention about it, but a description of the wood and bark anatomy of pulai up to the species level is hardly found. Anatomical structure of wood and bark of Alstonia scholaris, A. angustiloba and A. pneumatophora were observed on samples produced using a microtome. Dimensions of wood fiber and vessel cells also were measured. Observations showed that the three species of pulai wood can be distinguished from the differences in diameter and frequency of vessel cells, type and arrangement of parenchyma cells, width and composition of the ray cells. The bark of these species can be distinguisbed based on the form of sklereid cells and the presence of dilationed ray cells (widening ray cell).